The relations of antioxidant vitamins A, E, and C with MDA levels in serum and liver of rats treated with nitrosamines - Karahan, Izzet; Karataş, Fikret; Sakin, Fatih (My University, 2010)
In this study, we investigated the levels of vitamins A, E, and C in serum and liver, and malondialdehyde (MDA) were followed by long-term administration of some nitrosamines. Sprague-Dawley rats were divided into four groups. N-Nitrosodiethylamine (NDEA), 1-Nitrosopiperidine (NPip), and N-Nitrosopyrrolidine (NPyr) were administered 200 ppb, orally with water for 30 consecutive days to experimental groups. Animals were decapitated at 3rd, 7th, 15th, and 30th days of the administrations. Significant increases were observed in MDA levels treated with nitrosamines at all times. Serum MDA levels were found to be significantly higher in NDEA-treated animals than in control and other groups at 30th day. Liver MDA levels were highly increased in NPyr-treated group. Significant decreases were observed in the levels of vitamins A, E, and C in rats treated with nitrosamines at all times. There were also significantly negative correlations at present changes among the serum or liver MDA levels and vitamin A, E, and C levels in all nitrosamines-treated groups. These findings demonstrate that exposure at low levels of nitrosamines decreased vitamin A, E, and C levels while it attributed lipid peroxidation. Therefore, maintaining an adequate level of antioxidant vitamins in serum and liver may be necessary for the prevention or protection of long-term nitrosamine exposures. © 2010 Taylor & Francis.
Keywords: Lipid peroxidation; MDA; Nitrosamines; Vitamin A; Vitamin C; Vitamin E